1995
DOI: 10.1038/bjc.1995.192
|View full text |Cite
|
Sign up to set email alerts
|

A tumour-associated cell-surface glycoprotein accompanying p53 overexpression and higher growth potential for gastric cancer

Abstract: S aryTumour-associated cell-surface glycoprotein is associated with tumour progression in gastric cancer. We investigated the biological significance of tumour-associated cell-surface glycoprotein, determined by the binding of Helix pomatia agglutinin (HPA), with regrd to survival time and to the malignant potential of cancer cells in serosally invasive gastric cancer in 119 patients. HPA was positively stained in 75 of 119 patients (63.0%) with gastric cancer with serosal invasion. In patients with HPA-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
(10 reference statements)
1
11
1
Order By: Relevance
“…In esophageal cancer, there is no association between patient survival and p53 overexpression [25, 26, 33, 34]. However, most articles demonstrate that the p53-positive group shows worse survival in gastric cancer [27, 28, 35, 36]. We need a careful evaluation of p53 overexpression in colon cancer, since completely opposite results are often reported.…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal cancer, there is no association between patient survival and p53 overexpression [25, 26, 33, 34]. However, most articles demonstrate that the p53-positive group shows worse survival in gastric cancer [27, 28, 35, 36]. We need a careful evaluation of p53 overexpression in colon cancer, since completely opposite results are often reported.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Survival time for p53-positive patients (n = 115) was shorter than for p53-negative patients (n = 138) in those in the node-positive group (P = 0.0060). Solid line, p53-negative patients; light line, p53-positive patients The p53 abnormal staining was reported to be related to the proliferating activity of cancer cells (Kakeji et al, 1993), and aggressive behaviour of cancer cells for serosal invasion, lymph node metastasis of gastric cancer and a poorer prognosis ensued (Martin et al, 1992;Starzynska et al, 1992;Joypaul et al, 1994;Maehara et al, 1995;Mšnig et al, 1997). Because vascular and lymphatic involvement are closely related to p53 expression, p53 expression was closely related to tumour invasion and metastasis and, in particular, proved to be a significant prognostic factor for node-positive cases.…”
Section: Figurementioning
confidence: 99%
“…The loss of p53 function is related to the progression of the tumor by allowing cells with damaged DNA to continue to multiply (23). In some studies, p53 expression in stomach cancer has been reported to be bad prognosis (9)(10)(11)(12)(13)(14), but other reports have shown that p53 expression has no effect on clinical results (24)(25)(26). The reasons for these conflicting results are unclear.…”
Section: Discussion Discussionmentioning
confidence: 43%
“…Mutation in the p53 gene is one of the most common genetic lesions associated with gastric cancer, and some studies have reported that the expression of p 53 is related to bad prognosis (9)(10)(11)(12)(13)(14).…”
Section: Introduction Introductionmentioning
confidence: 99%